EM BUSCA DO ELEMENTO ESSENCIAL NA ESTRUTURA DA NORMA JURÍDICA PARA A CARACTERIZAÇÃO DO SEU CONCEITO (Reflection and Critique Law Magazine, 2024)
This article deals with the theme structure of the legal norm, in order to differentiate it from other social norms, based on the Theory of Legal Fact, which argues that the essential elements of the structure of the legal norm are the factual support and the precept. Yet this theory holds that the incidence of legal norms constitutes the specific difference that distinguishes them from other norms of social coexistence and other processes of social adaptation. On the other hand, the Pure Theory of Law holds that the essential element of the structure of the legal norm is sanction. The research methodology used in the study is the bibliographic that focuses on the theme. It is intended to present in a didactic and clear way the elements that make up the structure of the norm among renowned and consecrated authors with their theoretical proposals. In addition, the research makes a study to differentiate legal and natural law, describes basic normative orders, exposes doctrinal criticism of sanction as an essential element of legal rule, establishes differences between rules and principles, and addresses the concepts of factual support, precept and incidence. From this perspective, it is shown that there is no consensus in the doctrine about an essential element in the structure of the legal norm, which will differentiate it from the conventional norms, in order to arrive at the uniform concept, given the constitutive complexity around the legal norm structure. , since each indoctrinator has his own conviction.Keywords: Legal rule - Sanction - Legal Fact - Factual support - Precept.